First limits on light dark matter interactions in a low threshold two-channel athermal phonon detector from the TESSERACT Collaboration - Bui, Tuan Khai; Chang, C. L.; Chang, Y.-Y.; Chaplinsky, L.; Fink, C. W.; Garcia-Sciveres, M.; Guo, W.; Hertel, S. A.; Juigne, L.; Kavner, A. R. L.; Li, X.; Lin, J.; et al. (Physical review letters, 2025)
We present results of a search for spin-independent dark matter-nucleus interactions in a 1 cm2 by 1 mm thick (0.233 g) high-resolution silicon athermal phonon detector operated above ground. For interactions in the substrate, this detector achieves an rms baseline energy resolution of 361.5⁢(4) m⁢eV (statistical error), the best for any athermal phonon detector to date. With an exposure of 0.233 g×12 hours, we place the most stringent constraints on dark matter masses between 44 and 87 M⁢eV/c2, with the lowest unexplored cross section of 4⁢×10−32 c⁢m2 at 87 M⁢eV/c2. We employ a conservative salting technique to reach the lowest dark matter mass ever probed via direct detection experiment. This constraint is enabled by two-channel rejection of low energy backgrounds that are coupled to individual sensors.
Veröffentlicht: 15. Oktober, 2025
Gesehen am 05.01.2026